Equilibrium solutions for microscopic stochastic systems in population dynamics - MirosŁaw Lachowicz; Tatiana Ryabukha (Mathematical Biosciences and Engineering)
The present paper deals with the problem of existence of equilibrium solutionsof equations describing the general population dynamics at the microscopic levelof modified Liouville equation (individually--based model) corresponding to a Markovjump process. We show the existence of factorized equilibrium solutions and discussuniqueness. The conditions guaranteeing uniqueness or non-uniqueness are proposedunder the assumption of periodic structures.